Korelasi Keterampilan Proses Sains dan Keterampilan Metakognitif Terhadap Hasil Belajar Kimia Pada Materi Titrasi Asam Basa di SMA - Widia Arta Siregar; Pasar Maulim Silitonga (Universitas Negeri Medan, 2019)
This study aims to determine whether there is a linear and significant relationship between science process skills and student chemistry learning outcomes; metacognitive skills with student chemistry learning outcomes; science process skills and metacognitive skills with student chemistry learning outcomes. The population in this study were all students of class XI Mathematics and Senior High School Angkasa 1 Lanud Medan consisting of 2 classes. The research sample is one class taken by purposive technique. Based on the results of data analysis, it is concluded that there is a linear and significant relationship between science process skills and chemistry learning outcomes with a correlation value of 0.621 (high correlation) and the contribution of science process skills by 38.56%. In addition there is also a linear and significant relationship between metacognitive skills on student chemistry learning outcomes with a correlation value of 0.5 (enough correlation) and the contribution of metacognitive skills by 25%. And there is also a linear and significant relationship between science process skills and metacognitive skills on student chemistry learning outcomes with a correlation value of 0.809 (high correlation) and a contribution of 65.44%.